An investigation of a 3D printed micro-wind turbine for residential power production - Mohammad Shalby; Ahmad A Salah; Ghayda’ A Matarneh; Abdullah Marashli; Mohamed R. Gommaa (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The wind energy sector is rapidly growing and has become one of the most important sources of renewable power production. New technologies are being developed to increase energy production. This study focuses on developing and evaluating a 3-D printed micro-wind turbine system for residential electricity production. The effectiveness of using Poly Lactic Acid material for model production was assessed using the SolidWorks environment. Then, three–dimensional CFD model was developed to simulate a micro-wind turbine. The CFD model was validated in good agreement against scale physical model experiments performed in a wind tunnel. The results demonstrated that the 5-blade micro-wind turbine design was the most effective under the tested conditions, with a low cut-in speed and the ability to operate under torque up to 70 N.m. Finally, the currently available manufacturing processes for micro-wind turbines have been evaluated. Future work should evaluate the performance of the MWT system under realistic conditions in a site test to determine energy production and total efficiency